Rothmannia macrophylla, a new record for Thailand - Khammongkol, Kwanjai; Chamchumroon, Voradol; Tetsana, Naiyana; Poopath, Manop; Sae Wai, Jarearnsak; Sungkaew, Sarawood (Thai Forest Bulletin (Botany), 2016)
Rothmannia macrophylla (Hook.f.) Bremek. (Rubiaceae), a new record for Thailand, is described and illustrated.